2004
DOI: 10.1074/jbc.m406612200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Prion Protein Ure2 Shows Glutathione Peroxidase Activity in Both Native and Fibrillar Forms

Abstract: Ure2p is the precursor protein of the Saccharomyces cerevisiae prion [URE3]. Ure2p shows homology to glutathione transferases but lacks typical glutathione transferase activity. A recent study found that deletion of the Ure2 gene causes increased sensitivity to heavy metal ions and oxidants, whereas prion strains show normal sensitivity. To demonstrate that protection against oxidant toxicity is an inherent property of native and prion Ure2p requires biochemical characterization of the purified protein. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 50 publications
8
117
1
Order By: Relevance
“…Further, it was found that formation of amyloid-like fibrils had negligible effect on the level of GPx activity detected for purified protein in vitro [64]. Taken together, this indicates that Ure2 GPx activity is maintained upon structural conversion to the aggregated prion form.…”
Section: Relationship Between Enzymatic Regulatory and Prion Functiosupporting
confidence: 48%
See 2 more Smart Citations
“…Further, it was found that formation of amyloid-like fibrils had negligible effect on the level of GPx activity detected for purified protein in vitro [64]. Taken together, this indicates that Ure2 GPx activity is maintained upon structural conversion to the aggregated prion form.…”
Section: Relationship Between Enzymatic Regulatory and Prion Functiosupporting
confidence: 48%
“…Recent studies have found that deletion of the URE2 gene increases the sensitivity of S. cerevisiae cells to heavy metals and cellular oxidants, such as hydrogen peroxide [60][61][62]; and a Ure2 homologue from Aspergillus nidulans, while lacking the nitrogen metabolite repression activity of Ure2, also contributes to heavy metal and xenobiotic resistance [63]. Peroxidase activity of Ure2 towards oxidant substrates including hydrogen peroxide as well as typical organic hydroperoxides, such as cumene hydroperoxide and tert-butyl hydroperoxide (t-BH), has been demonstrated for the purified protein in vitro, confirming the function of Ure2 as a glutathione dependent peroxidase [64].…”
Section: Ure2 As a Glutathione Transferasementioning
confidence: 82%
See 1 more Smart Citation
“…39,61,62 Ure2p displays glutathione peroxidase and glutaredoxin activities, in both the soluble and fibrillar state, and therefore contributes to cell protection against heavy metal ions and oxidant toxicity. [63][64][65] However, truncations within the N-terminal domain of Ure2p increased the glutaredoxin activity, 64 suggesting that the N-terminal domain is an important feature for the proper biological function of Ure2p. 62 Altogether, these data suggest that yeast PrDs contribute to the normal biological function of their corresponding proteins, although the extent of this contribution may not be easily detectable under normal growth conditions.…”
Section: The [Psi + ] and [Ure3] Prionsmentioning
confidence: 99%
“…In addition to this general defensive role, some GSTs are directly implicated in the oxidative stress response by way of their GPx function (2). Such GSTs effi ciently reduce inorganic and organic exogenous peroxides or eliminate endogenous lipid and fatty acid peroxides (3,5,8). Thus, GSTs provide general protection against electrophilic xenobiotics, toxic metals and peroxides, not only via conjugation or reduction with GSH, but also by alleviating the oxidative stress and subsequent lipid peroxidation often associated with exposure to xenobiotics.…”
Section: Introductionmentioning
confidence: 99%